Fragilidade no idoso internado e o significado de fragilidade para a equipe de enfermagem - Lana, Letice Dalla (2013)
Fragility Syndrome Aging is a clinical syndrome that causes damage in the physical, psychological and social, leading to functional decline being determined by social risk factors, biological, environmental and psychological. Objective: To detect the presence of the syndrome of frailty in elderly in patients and the definition of fragility in the perception of professional nursing in the emergency department. Methodology: A quantitative cross-sectional and elderly aged over 60 years and nurses of the Emergency Department of the São Lucas Hospital. Scale was applied to Edmonton to fragility and specific questionnaire for the elderly and Teixeira Scale for nurses. The data were analyzed using the Student t test, chi-square test or the Fisher exact Poisson regression model. The significance level was 5%. The study was approved by the Research Ethics Comeettee of PUCRS under number 139242. Results: Both groups showed a mean age of 72.81±8.29 years, ranging from 60 to 92 years, 55.2% male, 41.1% were married, 81% live with family, 72.4 % retirees or pensioners, 87.7% of patients with previous disease and with an average of 3.81 medications per day. The majority of elderly patients (66.26%) is situated in the range classed as moderate and severe weakness, 25 (15.34%) with mild weakness, 29 (17.79%) with moderate brittleness and 79 (48,47% ) with severe weakness. The factors associated with frailty were age (PR = 1.21, 95% CI: 1.03 to 1.42), marital status (PR = 1.19, 95% CI :1,02-1, 37), use of medications (PR = 1.16, 95% CI 1.02 to 1.31), infectious diseases (PR = 1.17, 95% CI 1.03 to 1.32), neoplasms (PR = 1.22, 95 %: 1.06 to 1.42) and hospital stay of one or two times in the last year (PR = 1.35, 95% CI 1.15 to 1.58) (PR = 1.30, 95% CI: 1, 10 to 1.53). Regarding the sample of 12 nurses, there was a group of average age 29±3.3 years, ranging between 23 and 34 years, with 83.3% female, 58.3% single, 66.7% natural from Porto Alegre city and 58.3% without post graduation completed. Nurses to be fragile, should be the criterion vulnerability to environmental stress, disease and falls (100%), have comorbidities (91.7%), at an advanced age (83.4%) and perform fewer social activities (75%). Regarding the characteristics of fragility must be unintentional weight loss (100%), self-reported fatigue (75%), decreased grip strength (66.7%), reduction of physical activity (91.7%), cognitive impairment (83.3%), depression (100%) and reduction of social relations (100%). Consequences of weakness involving the decline of functional capacity (100%), hospitalization (58.3%), disability (58.3%) and death (58.3%). Conclusion: The fragility is important public health problem and demand more studies focusing on its definition targeting assistance on the part of health professionals with quality and effectiveness.